Payroll Taxes, Social Insurance and Business Cycles - Michael C. Burda; Mark Weder (Verein für Socialpolitik, 2010)
Payroll taxes represent a major distortionary influence of governments on labor markets. This paper examines the role of payroll taxation and the social safety net for cyclical fluctuations in an nonmonetary economy with labor market frictions and unemployment insurance, when the latter is only imperfectly related to search effort. A balanced social insurance budget renders gross wages more rigid over the cycle and, as a result, strengthens the model's endogenous propagation mechanism. For conventional calibrations, the model generates a downwardly-sloped Beveridge curve as well as substantial volatility and persistence of vacancies and unemployment.
Keywords: E24; J64; E32; 330; Business cycles; labor markets; payroll taxes; unemployment